Nokautowanie obywateli. Kultura przemocy w Rosji i jej reprezentacja w utworze Natalii Kluczariowej Wagon Rosja - Kalita, Liliana (Studia Rossica Posnaniensia, 2025)
The purpose of this article is to analyse and interpret Natalia Klyucharyova’s work Wagon Russia (Россия общий вагон, 2007), in which the writer creates an image of state violence against citizens, especially the most vulnerable, i.e. single mothers, injured veterans, the elderly, people belonging to sexual minorities. The description focuses on forms of economic, structural and symbolic violence. These take the form of, for example, the failure of the state and its subordinate institutions to perform the function of caring for the elderly, the lonely, war veterans; excessive bureaucratisation of life; officials avoiding responsibility for the consequences of their decisions; inappropriate distribution of public funds; infringement of individual autonomy; infiltration of selected social groups; isolation and ridicule of those critical of the system. The authorities use media systems and social institutions for their actions, which impose a specific model of functioning on the citizen, fostering victimisation and consolidation of aggressive patterns in the group, causing fear and an increased sense of powerlessness. Violence is therefore becoming the dominant way in which politicians communicate with the public.